Analysis of the factors affecting drivers' queue-jumping behaviors in China. (July 2020) - Yang, Liping; Feng, Zhongxiang; Zhao, Xiaohua; Jiang, Kang; Huang, Zhipeng
Highlights: Attitudes on queue-jumping and traffic violations significantly affect queue-jumping. Drivers' risk perception is a key determinant of queue-jumping behaviors. Drivers' safety motivation have a strong effect on queue-jumping behaviors. Drivers' driving skill also significantly affect their queue-jumping behaviors. The direct effect of type A personality trait on queue-jumping is not significant. Abstract: In China, drivers' queue-jumping behaviors are very common. To explore the factors affecting drivers' queue-jumping, first, a driving attitude scale, a risk perception scale and a queue-jumping behavior scale were designed, and an existing Type A behavior pattern scale and a driver skill scale were also introduced. Second, these scales were used to collect empirical data, and 202 valid samples were obtained. Third, the reliability and validity of the developed scales were verified, and a structural equation model of drivers' queue-jumping behaviors was established to explore the interrelationships among the Type A personality trait, cognitions (including attitudes and risk perception), driver skills (including driving skill and safety motivation) and queue-jumping behaviors. The results showed that drivers' cognitions significantly affected their queue-jumping behaviors; specifically, drivers' attitudes toward queue-jumping and traffic violations positively correlated with their queue-jumping behaviors (β = 0.323, t = 3.470; β = 0.277, t = 3.072), while drivers' risk perception toward queue-jumping negatively correlated with their queue-jumping behaviors (β = −0.297, t = −3.889). Drivers' driving skill and safety motivation also significantly affected their queue-jumping behaviors (β = 0.198, t = 2.385; β = −0.355, t = −4.101). Although Type A personality trait had no significant effects on drivers' queue-jumping behaviors, it had significant effects on drivers' attitudes toward queue-jumping and traffic violations (β = 0.336, t = 4.720; β = 0.215, t = 2.873) and their risk perceptions toward queue-jumping (β = −0.232, t = −3.279). In other words, the Type A personality trait can indirectly affect drivers' queue-jumping behaviors through drivers' attitudes and risk perceptions toward queue-jumping. The results provided offer traffic administration departments a theoretical foundation for governing this behavior.